Polymer Technology Outlook Study: Face Shields for Responding SARS-CoV2 Pandemic: Polymer Technology Outlook Study: Face Shields for Responding SARS-CoV2 Pandemic - Silvana Dwi Nurherdiana (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2021)
The coronavirus disease 2019 (SARS-CoV2) has attracted most interest in current years due to the worst impact for the global public health. In this situation, the whole world requires wearing face shield and mask as the personal protective equipment, especially for medical personnel. Polymer technology have been introduced as a helping tool against SARS-CoV2 by producing healthcare product such as face shield as the first line of resistance due to it was cost effectiveness, sterile nature, versatility and easy to modify. This article clarifies the discussion about face shields in the polymer technology as the point of view and aims at providing a deeper understanding about polymer, polymeric material, synthesis methodology and its application for responding SARS-CoV2 pandemic in a form of face shields. The study of the synthesis route and methodology, chemical and physical properties of the polymer for face shields have also been described.